Hubungan Persepsi Guru Tentang Tipe Kepemimpinan Kepala Sekolah dan Kedisiplinan dengan Kinerja Guru Sekolah Dasar di Kabupaten Lampung Selatan - Karno, Dedi; Riswandi, Riswandi; Perdana, Ryzal (JURNAL INOVATIF ILMU PENDIDIKAN, 2023)
The problem in this study is the low performance of teachers in South Lampung District Elementary Schools. The purpose of this study was to analyze the relationship between teachers' perceptions of the principal's leadership type and teacher discipline with teacher performance in South Lampung District Elementary Schools. This research uses a quantitative approach, with a non-experimental design. The sampling technique with multistage random sampling so that the number of samples is 50 teachers in South Lampung Regency Elementary Schools. Data collection techniques use questionnaire techniques. First hypothesis testing through material validation and design performed First hypothesis testing and second data analysis using simple correlation techniques. Testing the third hypothesis  using  multiple correlation analysis tests  The results of the study obtained were (1) There was a significant relationship between teachers' perceptions of the principal's leadership type and teacher performance, (2) There was a significant relationship between discipline and teacher performance, and (3) There was a significant relationship between      Teachers' perceptions of the principal's leadership type and  teacher discipline simultaneously  with teacher  performance